Modal-based attention modulates the redundant-signals effect: Role of unimodal target probability. (February 2023) - Wang, Xueli; Wu, Yingnan; Xing, Zepeng; Cui, Xinzhong; Gao, Min; Tang, Xiaoyu
Multisensory integration includes two behavioral manifestations: the modality dominance effect and the redundant-signals effect (RSE). RSE is a multisensory improvement effect in which individuals respond more quickly and accurately to bimodal audiovisual (AV) targets than to unimodal auditory (A) or visual (V) targets. Previous studies have confirmed that RSE is the product of modality interactions between different modalities. The goal of this study was to systematically investigate the effects of the modality dominance manipulated by modal-based attention and unimodal target probability on RSE. The results showed that when paying attention to both the A and V modalities (Exp. 1), RSE was not significantly different between unimodal target probabilities. When selectively paying attention to the A modality (Exp. 2A), RSE was also not significantly different between unimodal target probabilities. However, when selectively paying attention to the V modality (Exp. 2B), the magnitude of RSE showed a significant decreasing trend with the increasing probability of V targets. Our study is the first to reveal that the unimodal target probability significantly modulates RSE in visual selective attention, and this modulatory effect of the unimodal target probability on RSE is opposite to the modulatory effect on the modality dominance effect.